Ion specific effects in trivalent counterion induced surface and solution self-assembly of the anionic surfactant sodium polyethylene glycol monododecyl ether sulfate. - Xu, H; Penfold, J; Thomas, R; Petkov, J; Tucker, I; Webster, JR; Grillo, I; Terry, A (2014)
The effect of different trivalent counterions, Al(3+), Cr(3+), Sc(3+), Gd(3+), and La(3+), on the surface adsorption and Al(3+), Cr(3+), and Sc(3+) for solution self-assembly of the anionic surfactant sodium polyethylene glycol monododecyl ether sulfate has been studied by neutron reflectivity and small angle neutron scattering. The strong binding and complexation between the trivalent counterions and the anionic surfactant result in significant micellar growth and the formation of surface multilayer structures at the air-water interface at relatively low counterion concentrations. Broadly similar surface and solution behaviors are observed for the different trivalent counterions. The evolution in the surface and solution structures in detail depends upon the nature of the counterion, its hydrated radius and its strength of binding. Exceptionally the addition of Cr(3+) counterions have a less pronounced effect. This is attributed to a greater reluctance for exchange within the primary hydration shell for Cr(3+) ions, which results in a shielding of the electrostatic interactions and a reduced surfactant-counterion binding.